2021
DOI: 10.35845/kmuj.2021.21177
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Difficult Topics in Anatomy and Their Solutions as Per Undergraduate Medical Students

Abstract: OBJECTIVE: To identify the topics difficult to understand in learning Anatomy and to investigate the reasons of difficulty and their possible solutions. METHODS: This descriptive observational study was conducted at Army Medical College, Rawalpindi, Pakistan from April to November 2019. Open ended and validated questionnaires were filled by 205 undergraduate medical students at the end of their academic year to ensure that complete course of anatomy including gross anatomy, histology and embryology were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…However, challenges related to resource allocation, political interference, and administrative complexities are consistent themes across multiple studies. (4,10,11) Our ndings echo concerns raised in previous research regarding the dependency on government nancing, delays in budget approvals, and the disruptive impact of political transitions on institutional stability. (5, 10) These challenges underscore the complex nature of healthcare reforms and the need for multifaceted solutions.…”
Section: Discussionsupporting
confidence: 76%
“…However, challenges related to resource allocation, political interference, and administrative complexities are consistent themes across multiple studies. (4,10,11) Our ndings echo concerns raised in previous research regarding the dependency on government nancing, delays in budget approvals, and the disruptive impact of political transitions on institutional stability. (5, 10) These challenges underscore the complex nature of healthcare reforms and the need for multifaceted solutions.…”
Section: Discussionsupporting
confidence: 76%
“…23 They are also not generally happy about having to draw histological diagrams. 24 In the current study also, the students found gross anatomy questions asked in exams to be more in line with what they had been taught, followed by histology and embryology. Qamar et al mentioned similar results regarding gross anatomy.…”
Section: Discussionsupporting
confidence: 63%
“…A study revealed that students faced the most difficulty in studying embryology, followed by gross anatomy and histology. 24 The current students were of the opinion that, gross anatomy teaching was mostly relevant to the questions asked in various modalities of exams, followed by histology and embryology. Waseem et al 25 reported contradictory results and documented that students ranked histology as less relevant compared to gross anatomy and histology.…”
Section: Discussionmentioning
confidence: 99%
“…1 Efforts should be made to develop innovative teaching methods and resources that facilitate the understanding and retention of anatomical information, such as interactive digital tools and spaced repetition techniques. 11,12 Limited clinical integration and reduced cadaveric dissection were also recognized as challenges by a considerable proportion of the respondents. These findings highlight the need to enhance the clinical relevance of anatomy education and provide ample opportunities for practical experiences, including cadaveric dissection.…”
Section: Discussionmentioning
confidence: 99%
“…5 Spaced repetition techniques, involving the use of digital flashcards or specialized software, can aid in retaining complex anatomical knowledge. 12 Integrating anatomy into clinical scenarios and case studies can bridge the gap between anatomical knowledge and clinical practice. Providing practical experiences, particularly through cadaveric dissection, can deepen students' understanding.…”
Section: Discussionmentioning
confidence: 99%